The study on optogenetic tachyarrhythmia termination under pathological conditions from the single cell to the whole heart. (25th November 2020) - Ordog, B; Nyns, E.C.A; Fontes, M.S; Van Den Heuvel, T; Bart, C.I; Van Brakel, T.J; Schalij, M.J; De Vries, A.A.F; Pijnappels, D.A
Abstract: Background: Ventricular tachyarrhytmias (VTs) are common among patients suffering from cardiac remodeling and cause significant morbidity and mortality. Current research and treatment options for such VTs are suboptimal, hence new strategies are urgently needed. Optogenetics offers efficacious means to control cardiac rhythm, including shock-free VT termination. However, this has not been demonstrated in diseased hearts in vivo, while clinical translation would not only require such demonstration, but also an in-depth understanding of cellular responses. Purpose: To assess the optogenetic response at the cardiac cell, tissue, and whole heart level in terms of rhtyhm control under pathological conditions by an integrative experimental platform including in vitro and in vivo models of cardiac disease. Methods: Remodeling was induced in neonatal rat ventricular cardiomyocytes (NRVMs) by phenylephrine (PE) exposure. Pathological conditions leading to ventricular remodeling were mimicked by transverse aortic constriction (TAC) surgery in adult rats. The light-activated ion channel ReaChR was ectopically expressed in NRVMs and in hearts of TAC and sham animals by viral vector-based gene delivery. Results: Electrical and structural remodeling was evidenced by elongated action potential durations (p<0.05) and increased cell capacitance (p<0.05) in PE-treated, but not in control cells (CTL). Light-induced ionic currents in ReaChR-expressing PE-treated and CTL NRVMs displayed comparable kinetic properties and current densities (p>0.05). Illumination (1 s) caused a sudden shift in membrane potential leading to a plateau at −7.3 mV for PE-treated and −18.9 mV for CTL cells (p>0.05). Hearts explanted from TAC animals showed increased average heart weight to body weight ratio, ventricular fibrosis and expression of hypertrophy markers (ANP, aSkMA, p<0.05), while tissue preparations showed significant APD increase compared to sham. In vivo gene delivery resulted in expression of the ReaChR-citrine transgene in ∼80% of isolated ventricular myocytes (VMs). Photocurrent densities were not different (p>0.05) in VMs from TAC and sham animals, which currents led to comparable shifts in membrane potential (65.3 mV for TAC and 63.9 mV for CTL). In line with this, illumination caused marked depolarization in tissue preparations (from −77.6 to −16.4 mV) in TAC animals as assessed by conventional sharp electrode measurements. Importantly, as anticipated, electrically-induced VT episodes could be terminated in open chest experiments in TAC animals (n=6; 76.3% of cases) by epicardial illumination in vivo. Conclusions: Key operational parameters of the optogenetic response remained unaffected in models of cardiac disease, which allowed efficacious optogenetic VT termination in the diseased rat heart exhibiting structural and electrical remodeling. These findings corroborate the translational potential of shock-free therapy of cardiac arrhythmia by optogenetics. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): This work was supported by personal funding from the Netherlands Organization for Scientific Research (NWO, Vidi grant 1714336 to D.A.P.). D.A.P. is also a recipient of the European Research Council (ERC), Starting grant (716509). Additional support was provided by the Netherlands Heart Institute (ICIN grant 230.148-04 to A.A.F.d.V.).